Influencia de la estrategia .didáctica "MORE SPEAKING" en el desarrollo de la habilidad oral del idioma inglés en estudiantes del sexto grado "B" nivel primaria de la l.E. 0620 - Aplicación del distrito de Tarapoto - 2011 - Rios Ramirez, Teresa Estela (2013)
The didactic strategy MORE SPEAKING arises as an altemative because of the absence of motivating strategies from teachers, where it is observed that the motivation is untied of the learning activities; according to that this strategy allows the development of the speaking skill of the English language through the connection of the motivation with the learning activities, achieving this way a significant learning. The problem, hypothesis and general objective have been structured by means of the relationship between the variables strategy MORE SPEAKING and the development of the speaking skill of the English language. The theoretical body of the didactic strategy MORE SPEAKING was systematized endowing it with a purpose, didactic processes and a theoretical support based on the philosophical, psychological and pedagogic foundation. The studied population was formed by 88 students and the sample by 25 students who were evaluated by means of a pre and post-test to determine the significant influence or not of the didactic strategy MORE SPEAKING in the development of the speaking skill of the English language. To measure the students of the six grade B didactic strategy, a pre-test was applied at the beginning and a post test at the end of the six strategy pedagogic workshops; the tests were made up of 30 items divided into four components. The investigation design was pre-experimental with a pre and post-test; with an experimental group, those groups were intact not equivalent. According to the statistical results in the chart Nº01 where a great progress is demonstrated between the Pre-test and the Post-test. For this reason in the results of the hypothesis test according to the chart Nº 6 reject the null hypothesis and the investigation hypothesis is accepted. That is to say that the application of the didactic strategy MORE SPEAKING incremented significantly the development of the speaking skill of the English language in the students of the six grade B primary level of the Educational lnstitution Nº 0620-Aplication of Tarapoto district.